Sesame Street: Old School - Volume 2 - Simon, Paul; Tomlin, Lily; Pryor, Richard (Abbey Home Media, 2009)
A second volume of complete episodes from the first years of the groundbreaking US kids' show that actually managed to entertain and educate at the same time. Join Bert, Ernie, Big Bird, Elmo and Oscar the Grouch - as well as '70s friends like Don Music, Roosevelt Franklin, Guy Smiley and Fat Blue - for a trip down memory lane while singing along to 'What's the Name of That Song' and 'Telephone Rock!'. You'll learn all about letters, numbers, loveable furry monsters and much, much more. [www.amazon.co.uk]
Keywords: DVD-Video